HUBUNGAN SAINS DAN AGAMA MENURUT SYAIKH HUSAIN AFANDÃŽ AL-JASR - Muhammad Hilal (LP3M IAI Al-Qolam Malang, 2015)
This article is aimed to examine if pesantren as an Indonesian-rooted institution of education has a unique view on the relation between Science and religion. Inquiring Syaikh Husain AfandÃ® Al-Jasrâ€™s thought, the question that is into account here is whether the relation of Science and religion is answered in a fixed way that could become a unique perspective of pesantren. Even though Syaikh Husain AfandÃ® Al-Jasr wrote his thoughts in terms of theologian â€œdefending Muslimâ€™s faithâ€, his opinion about the relation between Science and religion could be regarded as interesting because he did not prohibit Science to develop according to its nature. Keywords: Relationship, Science and Religion, Pesantren